The protective effects of low- and high-fermentable dietary fibers on fecal microflora with antibiotic disturbance in in vitro fecal fermentation. (November 2022) - Mao, Yu-Heng; Song, Fenglin; Song, Ang-Xin; Xu, Yixuan; Qiu, Xiaofen; Zhao, Mingzhu; Tian, Zezhong; Yang, Yan
Graphical abstract: Highlights: The utilization rate is GOS > INU > KGM > MC by fecal microflora. Low-fermentable fiber enhanced the viability of gut bacteria better with antibiotic perturbance. High- and moderate-fermentable fibers lowered the microbial diversity with antibiotic perturbance. Low-fermentable fiber induced higher productions of acetic acid and total SCFAs. Abstract: Antibiotics adversely affect intestinal communities and prebiotic fibers are effective to counteract the side effects of antibiotics. The effects of prebiotic fibers vary due to their molecular characteristics. This study compared the effects of three fibers with different fermentation rates on fecal microflora with the perturbance of antibiotics in vitro. The results showed that supplementation of the low-fermentable fiber (konjac glucomannan, KGM) enhanced the viability of several gut bacterial groups and increased the production of acetic acid and total SCFAs better than the high- (galactooligosaccharides, GOS) and moderate-fermentable fibers (inulin, INU) with antibiotic disturbance. The relative abundance of Bacteroidetes was significantly lowered after fermentation with GOS compared with KGM and INU in the presence of ampicillin. KGM fermentation also maintained the relative abundance of possible butyric acid producer Clostridium . These results suggest that low-fermentable carbohydrates confer better effects to relieve or counteract antibiotic influence on gut microbiome.